Investigation of Magnesium-Potassium Phosphates as Potential Nuclear Waste Form for the Immobilization of Minor Actinides - Hans-Conrad zur Loye; Petr Vecernik; Monika Kiselova; Vlastislav Kašpar; Hana Korenkova; Vlastimil Miller; Petr Bezdicka; Jan Šubrt; Natalija Murafa; Volodymyr Shkuropatenko; Sergey Sayenko (Inorganics)
Several recent studies have evaluated technologies of spent nuclear fuel processing specifically for solidifying transuranic (TRU) waste as a by-product of fission. Of the TRU group, plutonium and the minor actinides will be responsible for the bulk of the radiotoxicity and heat generation of spent nuclear fuel in the long term (300 to 20,000 years). In this study, we investigated magnesium potassium phosphate (MKP)-based compounds as host waste forms for the encapsulation of inactive trivalent Nd and Sm as analogues of the minor trivalent actinides, Am and Cm. Waste forms were fabricated under ambient atmospheric conditions by adding 5 wt.% of substances containing Nd or Sm via the following two routes: powder oxides and aqueous solutions of nitrate salts. Waste form performance was established using strength and aqueous medium leaching tests of MKP-based specimens. The MKP materials were analyzed by X-ray diffraction (XRD), scanning and transmission electron microscopy (SEM and TEM), energy-dispersive X-ray spectroscopy (EDS), and Raman spectroscopy. The waste forms exhibited a compressive strength of ≥30 MPa and were durable in an aqueous environment. The leachability indices for Nd and Sm, as per the ANS 16.1 procedure, were 19.55–19.78 and 19.74–19.89, respectively, which satisfy the acceptable criteria (>6). The results of the present room temperature leaching study suggest that MKPs can be effectively used as a host material to immobilize actinides (Am and Cm) contained in TRU waste.